Clostridium Butyricum miyairi bacteriocin treatment for Clostridioides difficile infections with clinical isolates: Insights from in vitro, ex vivo, and mouse model studies - Ching-Chi Lee; Yi-Chen Tu; Hung-Tsung Wu; Wen-Chien Ko; Hsiao-Chieh Liu; Pei-Jane Tsai; Hsiang-Ning Chang; I-Hsiu Huang; Yuan-Pin Hung (Journal of Global Antimicrobial Resistance, 2025)
Objective: The standard antimicrobial therapy for Clostridioides difficile infections (CDIs) is limited to oral fidaxomicin or vancomycin, but these agents are associated with high treatment failure and recurrence rates. Clostridium butyricum has been proven effective in many types of gastrointestinal disease. Due to its ability to not disrupt the gut microbiota, we hypothesized that the probiotic C. butyricum Miyairi produced bacteriocin (CBMB-B) can be a potential therapeutic agent against CDIs. Methods: The inhibitory effects of CBM-B and vancomycin were compared using the kinetic time-kill assay, ex vivo co-culture model and mouse model. Results: Among the clinical isolates of C. difficile, the minimal inhibitory concentration (MIC) of CBM-B ranged from 0.0625 to 8 µg/mL; the MIC50 and MIC90 were 1 µg/mL and 4 µg/mL, respectively. In a mouse model where the animals were infected with various C. difficile strains belonging to RT178 and receiving CBM-B intra-rectally, mice infected with isolates with a relatively low CBM-B MICs (2 µg/mL, abbreviated as M2) revealed significant better therapeutic effect, including less loss of body weight and cecum weight, compared with those infected with isolates of relative high CBM-B MICs (4 or 8 µg/mL, abbreviated as M4 or M8). The relative C. difficile bacterial burden in stool of mice receiving CBM-B treatment were significantly lower among mice infected with M2, compared with that infected with M4 or M8. CBMB treatment, compared with vancomycin therapy revealed less disturbance in gut microbiota. Conclusion: CBMB-B could be effective in the treatment of CDIs where infections were caused by C. difficile isolates with relative low MICs.